Personalization of therapy for infections caused by N. gonorrhoeae, C. trachomatis, M. genitalium and T. vaginalis. Part II. Evaluation of the clinical effectiveness of personalized therapy - E.S. Negasheva; N.V. Frigo; A.E. Guschin; A.Yu. Khachaturyan; I.R. Baskakova; O.V. Zhukova (Russian Journal of Clinical Dermatology and Venereology, 2026)
Background. Currently used antimicrobial agents, their doses, and treatment durations are clearly defined by standards and clinical guidelines. Nevertheless, treating patients with sexually transmitted infections presents significant challenges despite the availability of highly effective drugs. In this connection, the transition to personalized treatment is relevant, which is consistent with the provisions of the Strategy for Research and Technological Development of the Russian Federation adopted in 2024. Objective. To evaluate the treatment outcomes for patients with uncomplicated gonococcal, chlamydial, M. genitalium infections, and trichomoniasis using the proposed personalized treatment algorithm (PTA) (study group) and clinical guidelines (CG, control group). Material and methods. The study included 1539 patients who received outpatient treatment for sexually transmitted infections at the Moscow Scientific and Practical Center of Dermatovenereology and Cosmetology (MSPCDC) in 2021—2024, with uncomplicated gonococcal (n=245), chlamydial (n=799), MG infection (n=379), and trichomoniasis (n=116). The first group (study) included 716 patients who received a personalized approach to therapy depending on the concentration of DNA of pathogens in the urogenital tract: higher doses of antimicrobial drugs and longer courses of therapy for high DNA concentrations (>104 gEq/ml) and lower doses and shorter courses for low DNA concentrations (